SOLID-PHASE SYNTHETIC APPROACH TO THE SYNTHESIS OF AZEPINE HETEROCYCLES OF MEDICINAL INTEREST - NAVJEET KAUR (International Journal of Pharma and Bio Sciences, 2013)
Solidphase organic synthesis is a rapidly expanding area of synthetic chemistry which is being widely exploited in the search for new medicinally important compounds by combinatorial techniques. In recent decades, a large number of reports related to solid-phase synthesis of heterocycles have appeared owing to a wide variety of their biological activity. In this review, we report the important role of solid-phase synthesis in the synthesis of azepine ring containing heterocycles.